Analisis Tata Letak Fasilitas Peternakan Sapi Juara Farm; Kabupaten Bogor Melalui Metode ARC dan TCR - Riskika Zahra Gusmayanti; Miranda Atmanegara; Mohamad Anas Hidayat; Melinda Bunga Eisya; Khoirul Aziz Husyairi; Tina Nur Ainun (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Layout has an important role in improving the quality of life and productivity of cows. Placing the right layout of space or facilities can make it easier to carry out daily maintenance and upkeep activities. This research was conducted to analyze the layout of facilities at Sapi Juara Farm. Sapi Juara Farm is a privately owned dairy farm located in Kec. Pamijahan, Bogor Regency, West Java. This farm provides fresh cow's milk to meet the demands of the cow's milk processing industry and the community's demand for milk. The layout of this farm needs to be reviewed in order to increase operational efficiency and optimal milk yield. This research aims to investigate and analyze the layout of facilities at Sapi Juara Farm using the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR) methods. The results of the analysis of the two methods showed that the highest score was in the feed warehouse with a total score of 331 and the lowest score was in the owner's house with a total score of 15. The equipment warehouse underwent changes to be placed adjacent to the sterilization room to make it easier to clean the equipment and the process of transporting the milk out.